Reflections on issues related to international affairs - Zamir, Muhammad, 1945- (Dhaka : Nymphea Publication, 2011)
Compilation of newspaper and journal articles on international affairs; appeared between October 2006 and March 2010.
Includes index.
Keywords: World politics -- 21st century